Participatory action research for educational leadership : using data-driven decision making to improve schools - James, E. Alana; Milenkiewicz, Margaret T.; Bucknam, Alan. (Los Angeles : Sage Publications, 2008)
Provides a readable overview of the PAR process similar to professional learning communities in schools. This title features its design that reaches out to visual learners as graphic elements guide graduate students through the research methods they need to successfully complete rigorous projects
Includes bibliographical references
Keywords: Action research in education; Educational leadership